The lean body mass to visceral fat mass ratio is negatively associated with cardiometabolic disorders: a cross-sectional study - Ya Shao; Na Wang; Meiling Shao; Bin Liu; Yu Wang; Yan Yang; Longti Li; Huiqin Zhong (Scientific Reports)
Abstract The literature has documented conflicting and inconsistent associations between muscle-to-fat ratios and metabolic diseases. Additionally, different adipose tissues can have contrasting effects, with visceral adipose tissue being identified as particularly harmful. This study aimed to explore the relationship between the ratio of the lean mass index (LMI) to the visceral fat mass index (VFMI) and cardiometabolic disorders, including dyslipidemia, hypertension, and diabetes, as previous research on this topic is lacking. This cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) conducted in the United States and included 10,867 individuals. Logistic regression was employed to explore the association between LMI/VFMI and cardiometabolic disorders. Generalized additive models were utilized to examine the nonlinear relationships between variables. Data analysis revealed a consistent inverse association between ln(LMI/VFMI) and dyslipidemia, hypertension, and diabetes. Each 2.7-fold increase in LMI/VFMI (one unit of ln[LMI/VFMI]) was associated with lower odds ratios (ORs) for these conditions. In men, the ORs were 0.21 (95% CI 0.17–0.25) for dyslipidemia, 0.37 (95% CI 0.30–0.45) for hypertension, and 0.16 (95% CI 0.10–0.23) for diabetes. Similarly, in women, the ORs were 0.22 (95% CI 0.19–0.26), 0.51 (95% CI 0.42–0.61), and 0.19 (95% CI 0.13–0.27). Quartile analysis showed that participants in the highest quartile (Q4) had significantly lower ORs compared to those in the lowest quartile (Q1). In men, Q4 ORs were 0.18 (95% CI 0.14–0.23) for dyslipidemia, 0.30 (95% CI 0.23–0.39) for hypertension, and 0.11 (95% CI 0.06–0.20) for diabetes. In women, Q4 ORs were 0.12 (95% CI 0.10–0.15), 0.39 (95% CI 0.29–0.52), and 0.12 (95% CI 0.06–0.25), respectively. Dyslipidemia and diabetes demonstrated nonlinear patterns, while a linear association was found for hypertension. Subgroup analyses across various characteristics confirmed these findings with no substantial directional changes. Maintaining an appropriate ratio of LMI to VFMI may be associated with favorable metabolic health.